Technical Skill Analysis (TSA) - Ahmad, Mohd Khir (Universiti Teknologi Petronas, 2011)
The purpose of the document is to show the basic idea of development, implementation and reaction of Technical Skill Analysis system, an online performance appraisal system project. The project will be implementing for all staff under Regulation Group of Bursa Malaysia. Technical Skill Analysis is developed to allow user to create an efficient way while conducting the performance appraisal process. Currently, the process for decision making consumes a lot of time and inefficient. Therefore, the time decision making for user to generate analysis and action plan affect the whole process. The problem faced by the Regulation Group of Bursa Malaysia was current performance appraisal method do not support the institutionalization of desired organizational direction. There are a problems in term of effectiveness, security and decision making process which consume a lot of times for analysis part. The scope of study of the project will be among staff of Regulation Group of Bursa Malaysia where the system will be implemented and later will use by them. The research methodology used was throw-away prototyping methodology. The procedures developed for this project were aimed at overcoming problem faced with the current performance appraisal process and at the same time continuing develop the system in order for developer to save time. This was achieved by evaluating the need for performance appraisals, problems associated with various methodologies and examining the qualities that need to be measured, both in terms of the individual and organization and identifying means of improving organizational performance. The study on how the implementation of this new performance appraisal system will help for a better performance appraisal process will also be discussed in the paper. The research found that the implementation of TSA ease a lot of process and consume less time yet improved security and effectiveness. As a result, it affects the decision making process and management consequences actions. From the research, it is recommended that current performance appraisal systems be redeveloped to focus on process, outputs, system has own stand-alone server and will expanded to whole company in the future.